Nanay na si Nene (A Journey to Early Motherhood): Understanding Pregnancy Through the Lens of Teenage Mothers - Aldaba, Colleene Shaey; Malasan, Rysa Cassandra; Salazar, Emmanuel Jerald; Teaño, Carissa Isobel; Villarama, Joseph (Journal of Interdisciplinary Perspectives, 2025)
Teenage pregnancy is considered one of the problems in the Philippines, which shows the necessity of understanding the frustrating implications. Employing a phenomenological research design, this research provides an overview of the emotional and social impacts that young mothers as teenage pregnancy may create, giving light on how it affects their psychological and life pursuits. This was achieved by utilizing semi- structured face-to-face interviews with eight (8) identified teenage mothers from Luzon, involving ten (10) self- developed and expert-validated questions designed to determine the impact of early motherhood on the emotional and social well-being of teenage mothers and the impact of early motherhood on aspirations and self-perception of teenage mothers. Their experiences and problems during pregnancy and the early phase of parenthood were analyzed. The findings highlighted the difficulties experienced by the youth, including their academic failure and the broad discrimination they face in society. Despite every mental, emotional, and investment difficulty, they also could reach strength from their families and partners. Inadequate comprehensive sex education, which creates a vicious circle, has a devastating impact on this issue. Albeit the adverse outcomes of teenage pregnancy, the results underline the importance of adequate sex education and support systems for teenage mothers. Such interventions are critical in averting unwanted adolescent pregnancies and ensuring healthier upbringing for future generations. Contrasting what teenage mothers go through and incorporating it into the policies, minimizes the kind of stigma faced by teenagers who fall victim to early pregnancies and creates a favorable and welcoming society for future generations.